Circulating Monocytes Serve as Novel Prognostic Biomarker in Pancreatic Ductal Adenocarcinoma Patients - Hansen, Frederik; David, Paul; Akram, Marina; Knoedler, Samuel; Mittelstädt, Anke; Merkel, Susanne; Podolska, Malgorzata; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; Kouhestani, Dina; Anthuber, Anna; et al. (Cancers, 2023)
Pancreatic ductal adenocarcinoma (PDAC) ranks among the most fatal cancer diseases, widely accepted to have the most dismal prognoses. Although immunotherapy has broadly revolutionized cancer treatment, its value in PDAC appears to be relatively low. Exhibiting protumoral effects, monocytes have recently been proposed as potential targets of such immunotherapeutic regimens. However, to date, the body of evidence on monocytes’ role in PDAC is scarce. Therefore, we analyzed monocytes in the peripheral blood of 58 PDAC patients prior to surgery and compared them to healthy individuals. PDAC patients showed increased levels of monocytes when compared to healthy controls In addition, patients with perineural infiltration demonstrated a higher percentage of monocytes compared to non-infiltrating tumors and PDAC G3 was associated with higher monocyte levels than PDAC G2. Patients with monocyte levels > 5% were found to have an 8.9-fold increased risk for a G3 and perineural infiltrated PDAC resulting in poorer survival compared to patients with <5% monocyte levels. Furthermore, PDAC patients showed increased expressions of CD86 and CD11c and decreased expressions of PD-L1 on monocytes compared to healthy individuals. Finally, levels of monocytes correlated positively with concentrations of IL-6 and TNF-α in plasma of PDAC patients. Based on our findings, we propose monocytes as a novel prognostic biomarker. Large-scale studies are needed to further decipher the role of monocytes in PDAC and investigate their potential as therapeutic targets.
CRIS-Team Scopus Importer:2023-02-03
Keywords: grading; liquid biopsy; monocytes; pancreatic ductal adenocarcinoma; perineural invasion; prognostic biomarker

Electrochemiluminescence in paired signal electrode (ECLipse) enables modular and scalable biosensing - Cho, Young Kwan; Kim, Hyunho; Benard, Alan; Woo, Hyun Kyung; Czubayko, Franziska; David, Paul; Hansen, Frederik; Lee, Jong Ik; Park, Jay Hoon; Schneck, Emmanuel; Weber, Georg; Shin, Ik Soo; et al. (Science Advances, 2022)
Electrochemiluminescence (ECL) has an inherently low background and enables precise chemical reactions through electrical control. Here, we report an advanced ECL system, termed ECLipse (ECL in paired signal electrode). We physically separated ECL generation from target detection: These two processes were carried out in isolated chambers and coupled through an electrode. The strategy allowed us to minimize cross-chemical reactions, design electrodes for high ECL signals, and integrate multiple sensors in a chip. As a proof of concept, we implemented an eight-plex ECLipse and applied it to detect host factors in human plasma. ECLipse achieved higher signal-to-noise ratio than conventional ECL assays and was >7000-fold more sensitive than enzyme-linked immunosorbent assay. In a pilot clinical study, we could detect septic conditions by measuring host factors [i.e., interleukin-3 (IL-3), IL-6, and procalcitonin (PCT)]. ECLipse assay further revealed distinct IL-3 and IL-6 patterns in patients with severe acute respiratory syndrome coronavirus 2 infection.
CRIS-Team Scopus Importer:2022-09-30

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

IL-3: key orchestrator of inflammation - Podolska, Malgorzata; Grützmann, Robert; Pilarsky, Christian; Benard, Alan (Frontiers in Immunology, 2024)
Interleukin (IL)-3 has long been known for its hematopoietic properties. However, recent evidence has expanded our understanding of IL-3 function by identifying IL-3 as a critical orchestrator of inflammation in a wide array of diseases. Depending on the type of disease, the course of inflammation, the cell or the tissue involved, IL-3 promotes either pathologic inflammation or its resolution. Here, we describe the cell-specific functions of IL-3 and summarize its role in diseases. We discuss the current treatments targeting IL-3 or its receptor, and highlight the potential and the limitations of targeting IL-3 in clinics.
CRIS-Team Scopus Importer:2024-07-12
Keywords: cancer; CD123; infection; inflammation; interleukin-3

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

Interleukin-3 protects against viral pneumonia in sepsis by enhancing plasmacytoid dendritic cell recruitment into the lungs and T cell priming - Benard, Alan; Hansen, Frederik; Uhle, Florian; Klösch, Bettina; Czubayko, Franziska; Mittelstädt, Anke; Jacobsen, Anne; David, Paul; Podolska, Malgorzata; Anthuber, Anna; Swierzy, Izabela; Schaack, Dominik; et al. (Frontiers in Immunology, 2023)
Rationale: Sepsis, a global health burden, is often complicated by viral infections leading to increased long-term morbidity and mortality. Interleukin-3 (IL-3) has been identified as an important mediator amplifying acute inflammation in sepsis; however, its function in the host response to viral infections during sepsis remains elusive. Objectives: To investigate the role of IL-3 during viral pneumonia in sepsis. Methods: We included septic patients from two different cohorts and used in vitro and in vivo assays. The obtained data were substantiated using a second model (SARS-CoV-2 infections). Measurements and main results: Low plasma IL-3 levels were associated with increased herpes simplex virus (HSV) airway infections in septic patients, resulting in reduced overall survival. Likewise, Il-3-deficient septic mice were more susceptible to pulmonary HSV-1 infection and exhibited higher pulmonary inflammation than control mice. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating plasmacytoid dendritic cells (pDCs) into the airways and by enhancing pDC-mediated T cell activation upon viral stimulation. Interestingly, the ability of IL-3 to improve adaptive immunity was confirmed in patients with SARS-CoV-2 infections. Conclusion: Our study identifies IL-3 as a predictive disease marker for viral reactivation in sepsis and reveals that IL-3 improves antiviral immunity by enhancing the recruitment and the function of pDCs.
CRIS-Team Scopus Importer:2023-03-24
Keywords: interleukin-3; plasmacytoid dendritic cells; sepsis; T cell priming; viral pneumonia

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Pleural Resident Macrophages and Pleural IRA B Cells Promote Efficient Immunity Against Pneumonia by Inducing Early Pleural Space Inflammation - Benard, Alan; Podolska, Malgorzata; Czubayko, Franziska; Kutschick, Isabella; Klösch, Bettina; Jacobsen, Anne; Naschberger, Elisabeth; Brunner, Maximilian; Krautz, Christian; Trufa, Denis; Sirbu, Horia; Lang, Roland; et al. (Frontiers in Immunology, 2022)
Airway infection is a major cause of mortality worldwide. The identification of new mechanisms aiding in effective host immune response is therefore required. Here, we show that the specific depletion of the pleural immune cell compartment during bacterial pneumonia resulted in a reduced pulmonary immune response and increased mortality in mice. Bacterial airway infection provoked early pleural space (PS) inflammation characterized by innate response activator (IRA) B cell development and pleural large resident macrophage (LRM) necroptosis, the repopulation of LRMs being driven by cellular proliferation in situ. Necroptotic LRMs amplified PS inflammation by stimulating pleural Mincle-expressing macrophages whereas IRA B cells contributed partially to GM-CSF-induced PS inflammation. Upon pulmonary infection, the induction of PS inflammation resulted in reduced bacterial burden whereas the specific depletion of pleural resident macrophages led to increased mortality and bacterial burden and reduced pulmonary immunity. Moreover, mice in which B cells were unable to produce GM-CSF exhibited reduced CD103+ dendritic cells and reduced CD4+ T cell numbers in the draining lymph node. Altogether, our results describe a previously unrecognized mechanism of pleural space inflammation necessary for effective protection against bacterial airway infection.
CRIS-Team Scopus Importer:2022-05-13
Keywords: bacterial airway infection; IRA B cells; mincle; necroptosis; pleural resident macrophages; pleural space

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment